Alleviative effects of Bacillus coagulans strains on irritable bowel syndrome-unraveling strain specificity through physiological and genomic analysis - Jiang Cao; Leilei Yu; Jianxin Zhao; Hao Zhang; Wei Chen; Yuzheng Xue; Qixiao Zhai (Food Science and Human Wellness)
The high intraspecies heterogeneity of Baciillus coagulans leads to significant phenotypic differences among different strains. Thus, 6 B. coagulans strains were tested in the present study using an irritable bowel syndrome (IBS) animal model to determine whether the IBS-alleviating effects of B. coagulans strains are strain-specific. The results of this study showed that the ingestion of B. coagulans GBI-30, 6086, and B. coagulans CCFM1041 significantly alleviated IBS symptoms in mice. In contrast, other B. coagulans strains showed no or limited alleviating effects on IBS symptoms. According to our experimental results, the two main common features of these strains were as follows: 1) The resistance of vegetative cells to bile salts, and 2) ability to synthesize specific lipids and secondary metabolites. Screening strains based on these two indicators may greatly reduce costs and provide a basis for mining new functional B. coagulans strains. Our results also suggest that administration of B. coagulans could significantly regulate microbiota dysbiosis in animal models. Moreover, the close relationships between the gut microbiota, gut microbiota metabolites, and IBS were further confirmed in this study.